Community Facilitators and Volunteers as a Model for the Implementation of Local Government Development in West Papua - Winnie Cherie Adriana Rumbruren; Selvi Diana Meilinda; Dwi Agus Sumarno; Hendayana Hendayana (FOUNDAE (Foundation of Advanced Education), 2026)
Volunteer participation has become an important element in local development implementation, especially in regions where public service delivery faces geographical, institutional, and social constraints. In areas with dispersed communities, limited service capacity, and recurring health and disaster-related pressures, volunteers and community facilitators often support the implementation of government programs at the community level. This study examines how media visibility represents volunteer participation in local government development implementation in West Papua. Using media-based content analysis, this study mapped 55 publicly indexed news reports published in 2024–2025 based on volunteer role, location, period, source, and search query. The findings show that reported volunteer activities were concentrated in hub areas, particularly Sorong and Manokwari. Health-related activities, especially blood donation, dominated public reporting, while education, social support, and environmental activities received less attention. The media also tended to frame volunteering as institution-led and programmatic service rather than community-based mutual aid. These findings indicate that media visibility may create representational bias by privileging accessible locations, formal institutions, and standardized activities. This bias can affect how volunteer contributions are recognized in local development policy and may reduce attention to less visible community-based initiatives. The study contributes a repeatable media-based approach for identifying visibility bias in volunteer reporting and provides empirical insight for improving equity-oriented development implementation in geographically dispersed regions.